Observation of ferromagnetic ordering by fragmenting fluorine clusters in highly fluorinated graphene. (June 2018) - Feng, Qian; Zheng, Yongping; Li, Jiaxin; Jiang, Liqin; Lin, Yuda; Ye, Qingying; Chen, Luzhuo; Huang, Zhigao
Abstract: To synthesize nonmetallic magnets containing exclusively s -p orbitals with high magnetic moments and magnetic ordering is a great challenge in physics and material science. In this study, we report increased localized spin magnetic moments and observation of ferromagnetic ordering by annealing of fluorographene. It is found that the magnetic properties is sensitive to fluorine (F) distribution. The samples annealed at ca. 400–450 °C exhibits an interesting ferromagnetic state, attributing to the fragmentizing of big F clusters into many small F domains after thermo defluorination. There are high-intensity magnetic moments in the annealed samples because of the enhanced edge effect of small F clusters, which contribute to the magnetic ordering in fluorographene for a shrunken average spacing between localized moments. The increasing structure defects after annealing can be as new centers of small F domains, and greatly stabilize magnetically ordered state. Graphical abstract: Image 1